Action research on applying the interactive approach to develop listening skills for second-year non-english major students at Hanoi University of Industry - Nguyễn, Thị Thu Hà (H. : ĐHQGHN, 2017)
This study aims at investigating the impact of interactive processing on second-year students’ listening skills at Hanoi University of Industry. More specifically, the researcher strives to (1) investigate problems that the students may encounter while learning listening, and (2) examine the effects of applying the interactive process in teaching listening to the second-year students. To achieve the above mentioned objectives, an action research is conducted with the participation of 42 second-year students of class E6.1_K9 within twelve weeks. A pre-test, a post-test and two questionnaires are used as instruments to collect data for analysis. The findings show that there are six problems that cause difficulties to students in listening. They are (i) lacking of vocabulary, (ii) structures of spoken language, (iii) speech rate, (iv) various and unfamiliar accents, (v) stress and intonation, (vi) lacking of background knowledge about the topic. After interactive processing has been applied, the students’ scores in the post-test are higher than in the pre-test. Overall, the instruction of interactive processing improves their listening skills.